Neea itanhaensis (Nyctaginaceae, Pisonieae), a new species from São Paulo State, Brazil - Rossetto, Elson Felipe Sandoli; Santos, Patrícia De Oliveira; Costa, Daniel Silva; Ferraz, José Roberto (Phytotaxa, 2019)
A new species, Neea itanhaensis, is described from São Paulo State, Brazil. N. itanhaensis differs from the other Neea species by its inflorescences with verticillate branching and sessile or subsessile leaves with an acute or oblique base and prominent secondary veins on the abaxial surface that diverge at less than a 90º angle from each other. Illustrations and comments about the taxonomy, phenology, distribution, habitat, conservation status and etymology are provided for the new species.